A faster inoculation assay for Armillaria using herbaceous plants. Issue 1 (2nd January 2017) - Ford, Kathryn L.; Henricot, Béatrice; Baumgartner, Kendra; Bailey, Andy M.; Foster, Gary D.
ABSTRACT: Armillaria (honey fungus) is a virulent necrotrophic pathogen that causes Armillaria root disease. Conventional Armillaria inoculation assays use young saplings as hosts and consequently are cumbersome, frequently conducted outdoors, and take many years from establishment to analysis of infection. We have developed and evaluated a faster inoculation assay for Armillaria that uses herbaceous plants as hosts, is carried out in controlled conditions, and reduces experimental durations to 3 months. Plant species of known susceptibility to Armillaria and comparisons between virulent A. mellea and opportunistic A. gallica were used to validate the assay. Mortality and diagnostic symptoms of Armillaria root disease such as epiphytic rhizomorphs and mycelial fans were used to assess levels of infection. We also attempted to reduce assay preparation time by substituting woody inocula with agar inocula, but typical symptoms of Armillaria root disease were only observed on plants infected with woody inocula. Through our assay, we identified five new potential herbaceous hosts of Armillaria: Kniphofia hirsuta, Hordeum vulgare, Lobelia cardinalis, Nicotiana tabacum and Helenium hoopesii – further expanding the extensive list of plants with susceptibility to Armillaria and suggesting infection of herbaceous species may be more widespread than currently acknowledged.